(untitled) (Journal of Enam Medical College, 2017)
Background: The World Health Organization has endorsed the use of molecular methods for the detection of tuberculosis (TB) and drug resistant TB as a rapid method. In Bangladesh, the Xpert MTB/RIF assay has been implemented into reference laboratories for diagnosis of TB and also MDR TB. Objective: Drug resistant tuberculosis has long been a common problem prevailing in our country. The present study focused on the rapid identification of Mycobacterium tuberculosis as well as drug resistance. Materials and Methods: Sputum samples from a total of 107 cases, assumed as multi-drug resistance tuberculosis, were studied through GeneXpert assay. Results: Out of 107 cases, 91 (85.05%) were detected having M. tuberculosis ? 64 (59.81%) were rifampicin sensitive and 27 (25.23%) were rifampicin resistant. The sensitivity and specificity of the GeneXpert are 87.64% and 75% respectively. Conclusion: GeneXpert assay can be considered for the rapid diagnosis of drug resistant tuberculosis. J Enam Med Col 2017; 7(2): 86-89